Pengaruh Profitabilitas terhadap Nilai Perusahaan dengan Moderasi Pengungkapan Elemen-Elemen Integrated Reporting - Bhimantara, Gilang Ryanda; Dinarjito, Agung (E-Jurnal Akuntansi; Vol 31 No 4 (2021), 2021)
This paper aims to determine the effect of profitability on firm value and the moderation of disclosure of integrated reporting elements in influencing the relationship of profitability with firm value. The sample is representative of each sector using the purposive stratified sampling method. This research is a quantitative study using a sample of 86 companies listed on the Indonesia Stock Exchange (BEI). Data were analyzed using multiple linear regression and processed using the Stata 13 application. The results show that profitability has no effect on the value of the company. Investors still need to consider the information generated from profitability because of the option to put into retained earnings and dividend distribution that will be taken by the company. The other result state that the integrated reporting elements do not affect the relationship of profitability with firm value because the value of information in the disclosure element is not directly related to the financial information (numbers) of a company. Keywords: Profitability; Firm Value; Integrated Reporting.